Kewajiban dan Tanggungjawab Wali Amanat Terhadap Investor Pemegang Obligasi Menurut Undang-Undang Nomor 8 Tahun 1995 Tentang Pasar Modal - Qodrad Risqitullah (JOURNAL of LEGAL RESEARCH, 2022)
This thesis is descriptive normative legal research on the Trustees' duty to bondholder investors under the Capital Market Law, hence no hypotheses are needed. Data collecting strategies using library research to trace legal documents to books, periodicals, seminar papers, and related laws and regulations, notably in the Investment industry. Data management techniques include editing and categorizing data, followed by qualitative data analysis to draw a conclusion, which is that the Trustee's obligation to bondholder investors under the Capital Market Law is to act only for the benefit of all investors and avoid a conflict of interest between the trustee's interests and those of bondholder investors (duty of loyalty and good faith). According to the Capital Market Law, these include researching prospective issuers, determining the rights of debt/bond holders, and drafting contracts/agreements.